The Influence Of Use Of Montage Media On The Creativity Of Children In Group B RA Ash Shiddiq Cileunyi Bandung District - Utami, Ryani; Hayati, Tuti; Syam'iyah, Syam'iyah (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
This research is based on the problems found during the initial observation at RA Ash Shiddiq Group B, where children's creativity has not yet developed optimally, with most children unable to coordinate eye and hand movements. This is due to the lack of supporting media in learning activities, as the focus is more on the use of pencils and paper, as well as worksheets. The aim of this research is to determine the effect of using montage media on the creativity of children in Group B of RA Ash Shiddiq Cileunyi. This research uses a quantitative approach with a quasi-experimental research method, implemented using a nonequivalent control group design. The sample used consists of all children in Group B of RA Ash Shiddiq, totaling 28 children divided into two groups: Group B1 with 13 children as the control group and Group B2 with 15 children as the experimental group. The results of the research show that there is an influence of montage media on the creativity of children in Group B of RA Ash Shiddiq Cileunyi, Bandung Regency. Based on the results of hypothesis testing, it is obtained that at a significance level of 5%. Thus, the null hypothesis is rejected and the alternative hypothesis is accepted.